Quantitative Estimates of Younger Dryas Freshening From Lipid δ2H Analysis in the Beaufort Sea - Junjie Wu; Ruediger Stein; Julian P. Sachs; Matthew Wolhowe; Kirsten Fahl; Defang You (Geophysical Research Letters)
Abstract The leading hypothesis attributes the Younger Dryas (YD) event to a disruption in the Atlantic Meridional Overturning Circulation, driven by meltwater input from North America. Determining the origin, timing, and magnitude of YD freshening are crucial for understanding abrupt climate change. This study examines the δ2H values of specific lipids in response to freshwater discharge and provides a quantitative estimate of YD freshening, using a marine sediment core from the Canadian Beaufort Sea, a region with documented evidence of a YD flood event. A pronounced reduction in δ2H values of leaf wax lipids and microalgal dinosterol indicates marked freshening at the onset of the YD, with the YD flood and the melting Laurentide Ice Sheet likely reducing surface water salinity by ∼15–24. In contrast, salinity levels remained high and stable for the last 8 kyr, likely implying a drier climate in the Mackenzie River basin.